Allometry and morphometrics of clypeal membrane size and shape in Nicrophorus (Coleoptera: Silphidae). (29th July 2017) - Wormington, Jillian D.; Luttbeg, Barney
Abstract: Contests between same‐sex opponents over resources necessary for reproduction, as well interactions used to discern mate quality, often involve exaggerated traits wherein large individuals have disproportionately larger traits. This positive allometric scaling of weapons or signals facilitates communication during social interactions by accentuating body size differences between individuals. Typically, males carry these exaggerated traits, as males must compete over limited female gametes. However, in Nicrophorus beetles both males and females engage in physical contests over the vertebrate carcasses they need to provision and raise offspring. Male and female Nicrophorus beetles have extended clypeal membranes directly above their mandibles, which could serve as signals. We investigated the scaling relationships between clypeal membrane size and shape and body size for five species of North American burying beetle to determine whether clypeal membranes contain exaggerated body size information. We found that clypeal membranes for both sexes of all species scaled positively with body size (slope > 1). Three of the five species also displayed sexual dimorphism in aspects of clypeal membrane size and shape allometry despite lack of dimorphism in body size. In two dimorphic species, small male clypeal membranes were statistically indistinguishable from the female form. We conclude that colored clypeal membranes in Nicrophorus beetles do contain exaggerated body size information. Observed patterns of dimorphism suggest that males sometimes experience stronger selection on marking size and shape, which might be explained by life history differences among species. Abstract : Nicrophorus clypeal membranes exaggerate body size, sometimes more noticeably in males.